1996
DOI: 10.1097/00007890-199607150-00013
|View full text |Cite
|
Sign up to set email alerts
|

Safe Use of Hepatic Allografts From Donors Older Than 70 Years1

Abstract: Between March 1991 and August 1995, 36 livers from donors >/=70 years old were transplanted. In donors, we recorded the following risk factors: alanine aminotransferase > 120 and rising, dopamine dose > 15 microg/kg/min, hypotension (systolic blood pressure <80) >1 hr, stay in the intensive care unit >5 days and body mass index >/=27. In 35 recipients, we recorded pretransplant United Network for Organ Sharing (UNOS) status, cold/warm ischemia time, intraoperative blood loss, and occurrence of poor early graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
78
1
16

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(103 citation statements)
references
References 13 publications
8
78
1
16
Order By: Relevance
“…A progressive growth of cholestatic indexes, accompanied by simultaneously decreasing cytolitic activity, is a common and already described finding (4,16,19,21), with a significant influence on survival rates (21). Although a similar course was observed in some of our cases, this did not seem to determine differences in p.o.…”
Section: Use Of Very Aged Donors For Liver Transplantationsupporting
confidence: 69%
See 1 more Smart Citation
“…A progressive growth of cholestatic indexes, accompanied by simultaneously decreasing cytolitic activity, is a common and already described finding (4,16,19,21), with a significant influence on survival rates (21). Although a similar course was observed in some of our cases, this did not seem to determine differences in p.o.…”
Section: Use Of Very Aged Donors For Liver Transplantationsupporting
confidence: 69%
“…Recent series of OLTs performed with the use of donors older than 60 years old (3)(4)(5)16,17) and, in one case, an 87-year-old (7), show that graft recovery can be satisfactory. donors below the age of 50 yr, showing no substantial differences in terms of liver function recovery, incidence of PGNF or retransplantation and graft survival up to 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…3 Patient and graft survival rates were 88% and 83% respectively, also very similar to those obtained with young livers. 1,2 Although the rate of surgical complications was similar in both groups, and none of the sepsis complications previously described were observed, it was noted that the arterial thrombosis only occurred with old liver grafts, and that was caused by technical problems and not by graft arterial damage. 8 The present clinical study demonstrates good long-term results obtained with liver grafts from elderly donors, with times of ischemia close to 6 hours, and proves the suitability of these donors for any type of recipient, beyond their previous restriction to critical transplant patients.…”
Section: Discussionmentioning
confidence: 60%
“…The consideration of these facts, together with the aging of population and the reduced number of liver donors available, have resulted in the use of elder donors. [1][2][3][4] Although the early function of grafts from donors above 65 years of age has been proven to be as good as that obtained with grafts from young donors, 1,5 their late function is less known. …”
mentioning
confidence: 99%
“…2 The impact of age of a cadaveric or living donor on the outcome of liver transplantation and the results of liver resection in the elderly patients have been evaluated in only a few clinical studies and are subject to considerable discussion. Although one study failed to show any significant difference, 3 others have suggested an increased risk for primary non-function in liver transplant recipients receiving a graft from older donors. [4][5][6] In this context, it is of interest to note that a major characteristic of the aging process is a decline in the cellular capacity to respond to proliferative stimuli.…”
mentioning
confidence: 94%